2009
DOI: 10.1111/j.1747-6593.2007.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic matter in leachate from different treatment processes

Abstract: The main objectives of this study were to investigate the characteristics of dissolved organic matter (DOM) extracted from the leachate of different treatment process using the chemical and spectroscopic analysing methods. The humic acid (HA), fulvic acid (FA) and hydrophilic (HyI) were isolated and purified by the XAD-8 resin combined with the cation exchange resin method. The analytical results of fluorescence excitation-emission matrix spectroscopy (EEMs) revealed that the fluorescence peaks were protein-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…This index also showed that groundwater lacks polymer particles and it does not contain great amounts of compounds with carboxylic groups. This is consistent with other literature values of character of -3 C humic mg•dm -3 C total mg•dm -3 C humic mg•dm -3 C total mg•dm -3 C humic mg•dm - aquatic humic substances [Huo et al, 2009;Malcolm, 1990;Newcombe et al, 1997;Stevenson, 1994] and confirms low concentration of carbon in carboxylic groups in groundwater. The general trends shown by fractions from the water samples are similar, however, the percentage of carbon in aquatic humic substances differs (Table 2).…”
Section: Resultssupporting
confidence: 92%
“…This index also showed that groundwater lacks polymer particles and it does not contain great amounts of compounds with carboxylic groups. This is consistent with other literature values of character of -3 C humic mg•dm -3 C total mg•dm -3 C humic mg•dm -3 C total mg•dm -3 C humic mg•dm - aquatic humic substances [Huo et al, 2009;Malcolm, 1990;Newcombe et al, 1997;Stevenson, 1994] and confirms low concentration of carbon in carboxylic groups in groundwater. The general trends shown by fractions from the water samples are similar, however, the percentage of carbon in aquatic humic substances differs (Table 2).…”
Section: Resultssupporting
confidence: 92%
“…On the other hand, relative to that of the influent, the fluorescence peaks of humic-like substances (peaks C, D) shifted to the longer wavelengths and became more intense with increase in pH. The extension of fluorescence wavelengths implied an increase in aromatic poly-condensation and a higher degree of humification (Kang et al, 2002;Huo et al, 2009), suggesting the higher humification degree in the MBR process, particularly under alkaline conditions of mixed liquor. These findings were in good agreement with Amonette et al 2004, who reported a higher degree of humification in soils under alkaline conditions through the enhancement of condensation step in the humification process.…”
Section: Results and Discussion 31 Effects Of Mixed Liquor Ph On Thementioning
confidence: 99%
“…molecular weights (MW) of humic substances, proteins, carbohydrates and hydrophilic acids (He et al, 2006;Huo et al, 2009). Therefore, the removal of organic compounds from landfill leachate through effective treatment technologies is thus necessary prior to discharge into the receiving environment.…”
mentioning
confidence: 99%
“…On the contrary, peaks C, A, and M are associated with humic-and fulvic-like materials, which are not easily used by microorganisms [18]. Huo et al [25] showed that protein-like organic matter is readily removed by biological processing and humic-and fulvic-like matter can be removed by reverse osmosis. The ratio of P i,n for the humic-and fulviclike regions (Regions III and VI) to P i,n for the protein-like regions (Regions I, II, V, and IV) (P h /P p ) may hence be used to predict a treatment technique for wastewater.…”
Section: Selection Of Leachate Treatment Process During the Landfill mentioning
confidence: 98%